Fetal alcohol spectrum disorder: the importance of assessment, diagnosis and support in the Australian justice context. Issue 2 (3rd March 2020) - Reid, Natasha; Kippin, Natalie; Passmore, Hayley; Finlay-Jones, Amy
Abstract : Fetal alcohol spectrum disorder (FASD) is a neurodevelopmental condition with life-long implications. Individuals with FASD can experience communication, cognitive, behavioural, social and emotional difficulties that impact their functional capacity. Due to these brain-based impairments, previous research suggests that individuals with FASD are over-represented in the justice system. The current article outlines how individuals with FASD may experience inequities within the justice system, why assessment, diagnosis and intervention is important, and the role of health and justice partnerships in promoting more equitable outcomes for justice-involved individuals with FASD. Increased resources and collaborations between health and justice professionals are required to enable the provision of neurodevelopmental assessments for all complex presentations, including FASD.